2022
DOI: 10.3390/ijms23031396
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and Functional Analysis of Copper Stress Response in the Sulfate-Reducing Bacterium Desulfovibrio alaskensis G20

Abstract: Copper (Cu) is an essential micronutrient required as a co-factor in the catalytic center of many enzymes. However, excess Cu can generate pleiotropic effects in the microbial cell. In addition, leaching of Cu from pipelines results in elevated Cu concentration in the environment, which is of public health concern. Sulfate-reducing bacteria (SRB) have been demonstrated to grow in toxic levels of Cu. However, reports on Cu toxicity towards SRB have primarily focused on the degree of toxicity and subsequent elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 106 publications
1
11
3
Order By: Relevance
“…This is in agreement with the findings obtained in studies on Auricularia fibrillifera [ 78 ]. Tripathi et al suggested that the translation process is energy-consuming, and the downregulation of translation under drought stress saves energy [ 79 ]. However, the response mechanism of genes in the ribosomal pathway under drought stress is still unclear, and further investigation is needed to elucidate the underlying mechanism involved.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the findings obtained in studies on Auricularia fibrillifera [ 78 ]. Tripathi et al suggested that the translation process is energy-consuming, and the downregulation of translation under drought stress saves energy [ 79 ]. However, the response mechanism of genes in the ribosomal pathway under drought stress is still unclear, and further investigation is needed to elucidate the underlying mechanism involved.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the toxic nature of Cu toward the SRB (Zampieri et al, 2022). Copper metal completely inhibits SRB mixed culture at a concentration ~ 4 mg/L (Hao et al, 1994), and ~50% reduction in total cell protein was reported at a concentration of 15 μM of Cu(II) for Oleidesulfovibrio alaskensis G20 (Tripathi et al, 2022). In the case of O. alaskensis G20 growth rate decreased from 0.17 to 0.10 h −1 when the concentration of Cu(II) was increased upto 15 μM.…”
Section: Antagonism Between Copper Ions and Microbial Colonizationmentioning
confidence: 99%
“…Repressed energy conversion is a commonly observed phenomenon in SRB during Cu stress. A total of five genes (DVU3132, DVU3133, DVU2091, DVU2348, and DVU1081) in D. vulgaris Hildenborough (Chen et al, 2019) and lactate dehydrogenase (Dde_3239) in D. alaskensis G20 (Tripathi et al, 2022) involved in lactate oxidation were downregulated. Furthermore, the gene encoding for the 30 and 50s ribosomal protein was downregulated by ~90% in D. alaskensis G20.…”
Section: Copper Toxicity Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the genome-wide transcriptional adjustments during silver stress may link genomic data to biological processes and molecular networks. This approach can potentially unveil crucial gene regulatory targets that play significant roles in promoting heavy metal tolerance [ 14 ].…”
Section: Introductionmentioning
confidence: 99%